2014
DOI: 10.1242/jcs.139188
|View full text |Cite
|
Sign up to set email alerts
|

High resolution live cell imaging reveals novel cyclin A2 degradation foci involving autophagy

Abstract: Cyclin A2 is a key player in the regulation of the cell cycle. Its degradation in mid-mitosis relies on the ubiquitin-proteasome system (UPS). Using high-resolution microscopic imaging, we find that cyclin A2 persists beyond metaphase. Indeed, we identify a novel cyclin-A2-containing compartment that forms dynamic foci. Fö rster (or fluorescence) resonance energy transfer (FRET) and fluorescence lifetime imaging microscopy (FLIM) analyses show that cyclin A2 ubiquitylation takes place predominantly in these fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
6
34
0
Order By: Relevance
“…In accordance with the reported ongoing mitophagy in arrested mitotic cells (38), LC3 puncta have been observed in mitotic cells, although at a significantly decreased level compared to interphase cells (28, 29, 39, 40). While these may also represent inefficient autophagy inhibition, Loukil et al observed LC3, p62, and lysosomal markers colocalizing with Cyclin A2 foci during mitosis and found that autophagy partially contributes to mediating mitotic Cyclin A2 degradation (40).…”
Section: Autophagy Status During Cell-cycle Progressionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with the reported ongoing mitophagy in arrested mitotic cells (38), LC3 puncta have been observed in mitotic cells, although at a significantly decreased level compared to interphase cells (28, 29, 39, 40). While these may also represent inefficient autophagy inhibition, Loukil et al observed LC3, p62, and lysosomal markers colocalizing with Cyclin A2 foci during mitosis and found that autophagy partially contributes to mediating mitotic Cyclin A2 degradation (40).…”
Section: Autophagy Status During Cell-cycle Progressionsupporting
confidence: 90%
“…While these may also represent inefficient autophagy inhibition, Loukil et al observed LC3, p62, and lysosomal markers colocalizing with Cyclin A2 foci during mitosis and found that autophagy partially contributes to mediating mitotic Cyclin A2 degradation (40). Thus, an intriguing although highly controversial theory is the existence of distinct sites of active autophagy during cell division.…”
Section: Autophagy Status During Cell-cycle Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclins and CDKs are ubiquitinated and degraded through the proteasomal pathway to maintain cell‐cycle progression . Loukil et al reported that autophagy is a regulator of cyclin A2 degradation beyond the metaphase of the cell cycle in proliferating cells . We show that both of the autophagic and proteasomal degradation systems degrade cyclin D1, as demonstrated by MG132 and CQ treatment.…”
Section: Discussionsupporting
confidence: 54%
“…(22) Loukil et al reported that autophagy is a regulator of cyclin A2 degradation beyond the metaphase of the cell cycle in proliferating cells. (23) We show that both of the autophagic and proteasomal degradation systems degrade cyclin D1, as demonstrated by MG132 and CQ treatment. However, the subsequent suppression of the cell-cycle progression was only rescued by CQ treatment, but not by MG132 (Fig.…”
Section: Discussionmentioning
confidence: 66%